The Composition and the Structure of MCC/Eisosomes in Neurospora crassa - Yang, Qin; Kempken, Frank (Frontiers in Microbiology, 2020)
Eisosomes are protein-containing domains in the plasma membrane in fungi and algae. The function(s) of eisosomes remains unclear. In this study, six eisosome components and five other proteins that appear to be spatially and temporally associated with eisosomes were identified in the filamentous fungus Neurospora crassa. These findings demonstrated interspecific differences, as the yeast eisosomal components Can1, Pkh1/2 and Fhn1 were not among the eisosomal proteins in N. crassa, and one new eisosomal protein (glucosamine-fructose-6-phosphate aminotransferase, gene ID: NCU07366) was found. Based on modeling and bioinformatic analysis of the identified eisosome components, an eisosomal structural model in N. crassa is presented. Multiple functions of eisosomes, associated with cell wall synthesis, response and signaling, transmembrane transport and actin organization are discussed.